Intensity and prevalence of depressive states in cancer inpatients: a large sample descriptive study. (30th June 2016) - Muzzatti, B.; Mella, S.; Bomben, F.; Flaiban, C.; Gipponi, K.; Piccinin, M.; Busato, S.; Annunziata, M.A.
Abstract : In cancer patients, depression causes suffering during the whole disease trajectory and it also influences the personal perception of well‐being as well as treatment adherence. Consequently, its better definition is needed for planning more tailored supportive programmes. This study was aimed to provide information on depressive state intensity and prevalence in an heterogeneous sample of cancer inpatients. In addition, associations were studied between depressive state and different socio‐demographic and clinical factors. A total of 1, 147 consecutive adult cancer inpatients completed the Center for Epidemiologic Studies Scale on Depression together with a form for collecting socio‐demographic and clinical data. The mean score of depression was 16.9 ( SD  = 9.3). There were differences in depression intensity associated with gender ( p  < .001), age ( p  = .001) and cancer type ( p  < .001), but not with education level ( p  = .282) or marital status ( p  = .436). Of the entire sample 13.9% had depressive states; this percentage raised to 26.2% if a less stringent criterion was used. These data reinforce the importance of a clinical and research focus on depression in oncology. As differences according to gender, age and diagnosis exist in depression prevalence and intensity, tailored supportive intervention should be planned and verified for effectiveness and efficacy.